(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The article examines the conditions for a potential reintroduction in Italy of a Parliamentary Technological Assessment Body. Like most democratic legislative assemblies, the Italian Chambers have established bodies and procedures dedicated to processing the knowledge necessary for political decision-making. The article examines how the establishment of a parliamentary body dedicated to technical and scientific issues might fit into this context. To be successful, the establishment of the new body would need to carefully identify an appropriate combination of political input and technical expertise, as well as a positive integration into Parliament’s factfinding procedures.